The Contribution of Personality Macro-Factors in Predicting Marital Satisfaction of Women: A Preliminary Study for Developing a Premarital Counseling Protocol - Keyghobadi, Nasrin; Fatehizade, Maryam; Tabrizi, Mehdi (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study was conducted with the aim of examining the contribution of personality macro-factors in the variance of women’s marital satisfaction: a preliminary study for developing a premarital counseling protocol.Methods and Materials: The research method was descriptive-correlational. The statistical population included all married female students aged 25 to 40 who were studying at Islamic Azad Universities in Isfahan during the 2023–2024 academic year. From this population, 128 individuals were selected using Cochran’s formula and the convenience sampling method. They completed the Enrich Marital Satisfaction Questionnaire (1989) and Cattell’s 16 Personality Factors Questionnaire (1993). Data were analyzed using Pearson correlation tests and stepwise multiple regression analysis via SPSS-23.Findings: The results indicated that there was a positive relationship between the personality trait of extraversion and women’s marital satisfaction, and a negative relationship between the personality trait of self-control and women’s marital satisfaction. Moreover, the outcomes of regression analysis showed that the personality traits of self-control and anxiety, with determination coefficients of –0.401 and –0.220 respectively, were able to predict marital satisfaction.Conclusion: Considering the existence of a relationship between personality traits and marital satisfaction, the findings of this study can be used in premarital counseling. By identifying women’s personality traits, it is possible to predict and enhance their marital satisfaction.